Lexical Density in EFL Indonesian Textbooks: A Comparative Analysis - Ahmad Fadhil; Wawan Gunawan; Yanty Wirza (JALL (Journal of Applied Linguistics and Literacy), 2023)
The lexical density is known as the component determining the complexity level of the text. Hence, measurement of lexical density is needed to find out how challenging a particular text is to read.  However, it is important to know that the lexical density in English reading materials especially in Indonesian EFL textbooks between the Government Publisher and Non-Government Publisher is still less explored. This research will employ the Quantitative design to investigate how dense the lexical items are found in these two EFL Textbooks. The result showed that the lexical density of the non-government textbook is denser in all of the genres of the text compared to the government textbooks. In brief, by knowing the lexical density in the text, the teacher should have known what the appropriate text level should be taught to the students which is neither too low nor too high.